Navigating stress in the multi-device, multi-channel work environment: The role of subjective interruptedness and Fear of Missing Out at Work - Ebner, Katharina; Wehrt, Wilken; Soucek, Roman (International Journal of Workplace Health Management, 2025)
Purpose The rapid evolution of digital technology has transformed knowledge work into a multi-device, multi-channel environment with constant interruptions. While interruptions are recognized as detrimental to employee well-being, the relationship between IT-mediated interruptions and stress remains complex. This study investigates whether the frequency of interruptions or subjective perceptions of being interrupted contribute to daily stress, and explores the moderating role of Workplace Fear of Missing Out (FoMO) in amplifying stress responses. Design/methodology/approach Guided by Lazarus’ transactional model, we analyze the contributions of both, the (objective) frequency of IT-mediated interruptions and individuals’ subjective perceptions of being interrupted at work (i.e. interruptedness) to daily stress outcomes further considering that individuals who experience interruptedness as a threat will suffer particularly from negative effects due to high FoMO. To test the hypotheses, a five-day diary study with employees from knowledge professions was conducted. Multilevel analyses were employed to analyze the data. Findings Results revealed that the frequency of daily interruptions indirectly affects stress outcomes via perceived daily interruptedness, emphasizing the role of subjective experiences. FoMO emerged as a moderator, with individuals experiencing higher levels of FoMO reporting greater cognitive strain at the end of a workday. Originality/value The study highlights the critical role of the subjective interruption experience in shaping stress, and introduces FoMO as a relevant construct for understanding stress in multi-device, multi-channel work settings, offering actionable insights for fostering well-being at work.
Keywords: Interruptions; interruptedness; stress; FoMO; diary study